До поняття формату жанру інтерв’ю у журналістиці - Казімова, Юліана; Kazimova, Juliana (Видавництво Львівської політехніки, 2018)
Досліджено формат сучасного газетного інтерв’ю. Це питання актуальне сьогодні, адже, незважаючи на те, що є багато журналістських інтерв’ю, у яких чітко дотримано вимог жанру, проте є також випадки не професійно поставлених запитань, неготовності журналістів до проведення інтерв’ю, нелогічність постановки запитань. Для визначення специфіки підготовки журналістами ефективного інтерв’ю, досліджено формат цього жанру в журналістиці, проаналізовано ознаки інтерв’ю як жанру журналістики, охарактеризовано види інтерв’ю за комунікативним наміром (метою) і типом комунікативної стратегії, форми, за кількістю учасників, визначено правила проведення інтерв’ю та формулювання запитань.

This article explores the format of a contemporary newspaper interview. This question is relevant today, after all, despite the fact that there are many journalistic interviews that clearly meet the requirements of the genre, however, there are also cases of not professionally raised questions, the unpreparedness of journalists to conduct an interview, illogical questioning. To determine the specifics of the preparation of effective interviewing by journalists, the format of this genre in journalism is researched, characteristics of the interview as a genre of journalism are analyzed, types of interviews are described in terms of communicative intent (purpose) and type of communicative strategy, form, by number of participants, rules for interviewing and question formulation are defined.
To the concept of the format of the genre of interviews in journalism
Keywords: формат жанру; формат інтерв’ю; види інтерв’ю; ознаки жанру; ефективність жанру; format of genre; format of interviews; types of interviews; genre features; genre’s effectiveness; 070; 303.62